Engendering Peacebuilding in an Endangered Country: Strategic Interventions for Women Peace Activism in Nigeria - Mike Omilusi (ABUAD Journal of the Humanities-AGIDIGBO)
The recognition of women's peacebuilding activities, arguments for why women should be involved in peacebuilding, and the development of strategies for their inclusion, has been a dominant focus in the literature and activism of women engaged in the arena of development, peace and security. Women's involvement in peace and security processes in Africa has gained momentum over the last two decades largely as a direct consequence ofliving and/or working in conflict zones. In most wars, gender roles are strictly defined: women and children are seen as the victims, while men are viewed as both the perpetrators of violence and the peacemakers. Women take on many different roles in wartime and have diverse experiences. Nonetheless their experiences tend to be distinct from men's and also share a set of common vulnerabilities. In this paper, women's participation in peace building and conflict management is examined at both regional and national levels with specific reference to Nigeria. It argues that gender mainstreaming is particularly significant in its application to conflict transformation, as it is increasingly recognized at both the international and domestic levels that women and men do not experience conflict in the same way and have different needs and priorities in the aftermath. It submits that there is a need for peacebuilding to incorporate policies which address women's specific health and economic needs.